2019
DOI: 10.2147/cia.s201250
|View full text |Cite
|
Sign up to set email alerts
|

<p>Changes in the blood antioxidant defense of advanced age people</p>

Abstract: Introduction: Since 1956 there have been numerous scientific articles about free radical theory of aging which both confirm and deny the theory. Due to oxygen metabolism, there are relatively high concentrations of molecular oxygen in human cells, especially in mitochondria. Under normal physiological conditions, a small fraction of oxygen is constantly converted to ROS, such as superoxide radical (O2 −• ), H 2 O 2 , and related me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 71 publications
3
36
0
Order By: Relevance
“…In our study, the influence of age on decreased intracellular total SOD activity was shown ( Table S1 in Supplementary Materials ); this is consistent with other studies concerning animals and humans [ 38 , 39 ]. The changes in total SOD activity in elderly people may be caused by decreased SOD1 activity [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the influence of age on decreased intracellular total SOD activity was shown ( Table S1 in Supplementary Materials ); this is consistent with other studies concerning animals and humans [ 38 , 39 ]. The changes in total SOD activity in elderly people may be caused by decreased SOD1 activity [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the influence of age on decreased intracellular total SOD activity was shown ( Table S1 in Supplementary Materials ); this is consistent with other studies concerning animals and humans [ 38 , 39 ]. The changes in total SOD activity in elderly people may be caused by decreased SOD1 activity [ 38 , 39 ]. However, the increased total SOD activity in extracellular environment can be explained by increasing oxidative stress with aging, which underlines the important role of this enzyme in its neutralization [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Supplementary antioxidants add to the cellular antioxidant defense system, containing antioxidant enzymes, DNA repair, and low-weight antioxidants. Many studies suggest that this system declines with aging [19,20]. At present, clinical recommendations say that cancer patients, independently of age, should rather not take antioxidants during therapy [21][22][23].…”
Section: Nutrition Aging and Cancer In The Elderlymentioning
confidence: 99%
“…The study of Kozakiewicz et al . 29 clearly showed age-related changes including increase in intensity of TBARS with the simultaneous decrease of crucial activity of antioxidative enzymes. The present work investigated only non-smoking, healthy elderly patients with or without insulin-resistancy, and we found that insulin-resistant otherwise with good health elderly persons had lower TBARS concentration in comparison with insulin sensitive ones.…”
Section: Discussionmentioning
confidence: 98%